Investigation of the Effect of Upstream Slope and Bed Material on the Rate of Pollutant Release to Downstream Dams Using a Two-Phase SPH algorithm - Rahim Shamsoddini; Bahador Abolpour; Yi Zhao (Journal of Hydraulic Structures)
Most of the pollution of dams, lakes and even coastal water is related to their upstream bed. When floods and drifts occur, the pollutants in the bed are carried into these bodies of water. There are several factors that influence the rate at which these pollutants are emitted. Among these factors, the material and slope of the bed play a crucial role, yet they have not been thoroughly investigated until now. Therefore, this study aims to model this phenomenon and examine the aforementioned parameters using a Lagrangian numerical method. The numerical method developed is the Smoothed Particle Hydrodynamics (SPH). The flow consists of two phases, one phase is considered a Newtonian fluid while the other phase is considered a non-Newtonian fluid. Due to the momentum of the fluid and the sharp changes in the flow, turbulent flow is assumed, and by approximating and calculating the turbulent viscosity, its effects are considered in the modeling. In addition to the fluid motion equations, the concentration equation is also solved to calculate the emission rate. After validating the computational code, nine different cases are modeled and evaluated based on the bed material and the slope of the bed. The results show that the change in each of these parameters has a significant effect on the emission of pollutants.